1999
DOI: 10.1021/bi991378g
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Absorption, EPR, and Resonance Raman Spectroscopy of CooA, a CO-Sensing Transcription Activator from R. rubrum, Reveals a Five-Coordinate NO-Heme

Abstract: Electronic absorption, EPR, and resonance Raman spectroscopies revealed that CooA, the CO-sensing transcriptional regulator from Rhodospirillum rubrum, reacts with NO to form a five-coordinate NO-heme. NO must therefore displace both of the heme ligands from six-coordinate, low-spin Fe(II)CooA in forming five-coordinate Fe(II)CooA(NO). CO, in contrast, displaces a single heme ligand from Fe(II)CooA to form six-coordinate Fe(II)CooA(CO). Of a series of common heme-binding ligands, only CO and NO were able to bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
106
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 65 publications
18
106
0
Order By: Relevance
“…8) [66]. These simulated values are in good agreement with those of other 5c {FeNO} hemoproteins [63,64,[67][68][69][70]. No spectral changes were observed with changes in pH (data not shown).…”
Section: Fe(ii) Rhed Binds No(g)supporting
confidence: 82%
“…8) [66]. These simulated values are in good agreement with those of other 5c {FeNO} hemoproteins [63,64,[67][68][69][70]. No spectral changes were observed with changes in pH (data not shown).…”
Section: Fe(ii) Rhed Binds No(g)supporting
confidence: 82%
“…Six-coordinate S ϭ 1͞2 {FeNO} 7 species in heme proteins have much stronger Fe-NO bonds, as evidenced by (Fe-NO) frequencies in the range 536-558 cm Ϫ1 (20,21,41), and much weaker N-O bonds, as evidenced by (N-O) frequencies in the range 1,555-1,624 cm Ϫ1 (20,21). Although no clear consensus has emerged concerning the most appropriate description of the electronic structure and bonding in S ϭ 1͞2 {FeNO} 7 species (18,32,42), the increase in Fe-NO bond strength and concomitant decrease in the N-O bond strength, compared with S ϭ 3͞2 {FeNO} 7 species, appear to be a direct consequence of increased -donation into the empty d z2 orbital that results from lowering the Fe spin state from high to low or intermediate spin.…”
Section: Discussionmentioning
confidence: 99%
“…The UV-visible spectra of CO-, imidazole-, and CN Ϫ -bound ⌬P3R4 CooA were obtained with high pH anisotropy buffer for proper comparison with DNA binding activities of these forms. has been demonstrated that other potential exogenous ligands cannot create the 6-coordinate CooA adduct; NO is the only small molecule, other than CO, that can form a stable adduct to the heme of CooA (16), but NO binding results in a 5-coordinate form that appears to be inactive (16). This has led to the hypothesis that CO specificity results from its unique ability to create a 6-coordinate heme in CooA.…”
Section: Methodsmentioning
confidence: 99%
“…Small molecules that are weaker ligands than CO fail to displace the Pro 2 ligand, whereas NO displaces both protein ligands and leads to an inactive protein (16), and O 2 binding oxidizes CooA. It was therefore a reasonable hypothesis that the specificity for CO simply reflected its liganding strength.…”
mentioning
confidence: 99%